(3OhQ GdGJMGO GdChQhHj aj YGde eG HYO LGFMI (B"(3chajO(B-19" /s - (3HdGchjd, SJjafs ([(3GdEeGQGJ GdYQHjI GdeJMOI(B] :s (3eQcR JQjfOR ddHMhK hGdGSJTGQGJ,s, 2020)
(3jhVM GdcJGH Gfg cGf dhHGA (B"(3chajO(B-19 (3CKQ MGO Ydi Ohd GdGJMGO GdChQhHj ; aHGdEVGaI Edi GdJCKjQ GdUMj, SJONd GbJUGOGJ GdGJMGO MGdI QchO HSHH GdEZdGb, hGdELQGAGJ GdCNQi GdJj Je GJNGPgG dGMJhGA GdajQhS(B. (3aHYO QOI aYd ChdjI eQJHcI, fSbJ GdeDSSGJ GdQFjSjI aj GdGJMGO GdChQhHj YedjGJ EjUGd GdeSGYOGJ GdWHjI, hbOeJ MReI eGdjI cHjQI ddeSGYOI aj EfYGT GdGbJUGOGJ GdChQhHjI ; heY gPG, JWQM GdCReI GdQGgfI GdYOjO ef GdCSFdI Yf GdOhQ GdeSJbHdj ddGJMGO aj GdYGde(B. (3hJCSjSG Ydi fXGe bGfhfj eYbO, JYcS GdYdGbGJ GdNGQLjI ddGJMGO GdChQhHj GdbhI GdGbJUGOjI dCcHQ Shb ehMOI aj GdYGde(B. (3hdcf, Ydi GdQZe ef Cf GdGJMGO GSJNOe GdJLGQI dEMOGK CcHQ JCKjQ aj GdUabGJ eY GdOhd ZjQ GdCYVGA, aEf GdOhd GdCYVGA eG RGd YdjgG GdcKjQ ef GdYed MJi JWhQ SjGSGJ NGQLjI hOaGYjI aYGdI ddGJMGO ; hGdCeQ GdCge gh Cf GSJQGJjLjI GdGJMGO GdYGdejI JYJeO Ydi GdMaGX Ydi GdfXGe eJYOO GdCWQGa GdMGdj HGdJYGhf eY Gdbhi GdcHQi GdCNQi(B. (3hdPG aEf JCKjQ GdGJMGO GdChQhHj HGYJHGQg aGYdG OhdjG SjYJeO CjVkG Ydi bOQI GdOhd GdCYVGA Ydi GdMaGX Ydi JeGScgG hGdJZdH eYG Ydi GdCReI GdMGdjI(B.s
(3jTJed Ydi edGMb(B.s
(3jTJed Ydi edNU HGddZI GdYQHjI(B.s
(3jTJed Ydi HHdjhLQGajI(B.s
Keywords: (3YOGhi ajQhS chQhfGs -- (3Ohd GdGJMGO GdChQhHjs; (3ajQhS chQhfG GdeSJLOs -- (3hbGjI hecGaMIs -- (3Ohd GdGJMGO GdChQhHjs